2018
DOI: 10.1103/physrevc.98.025204
|View full text |Cite
|
Sign up to set email alerts
|

Robust extraction of the proton charge radius from electron-proton scattering data

Abstract: Background: Extracting the proton charge radius from electron scattering data, requires determining the slope of the charge form factor at Q 2 of zero. As experimental data cannot reach that limit, numerous methods for making the extraction have been proposed.Purpose: In this study, we seek to find functional forms that will allow a robust extraction of the proton radius from a wide variety of functional forms. The primary motivation of this study is to have confidence in the extraction of upcoming low Q 2 exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 49 publications
3
59
0
Order By: Relevance
“…The results of the dipole fits to the proton data shown in Fig. 36 give r p E ∼ 0.833 and r p M ∼ 0.795, which are roughly consistent with the careful analysis of electronexperiment results [43] given in Eqs. (13) and (14) and the Kelly fits shown in the bottom row of Fig.…”
Section: Appendix C: Esc In the Extraction Of The Form Factorssupporting
confidence: 83%
See 2 more Smart Citations
“…The results of the dipole fits to the proton data shown in Fig. 36 give r p E ∼ 0.833 and r p M ∼ 0.795, which are roughly consistent with the careful analysis of electronexperiment results [43] given in Eqs. (13) and (14) and the Kelly fits shown in the bottom row of Fig.…”
Section: Appendix C: Esc In the Extraction Of The Form Factorssupporting
confidence: 83%
“…Electromagnetic form factors of nucleons are extracted from differential cross-sections measured in the scattering of electrons off nuclei. The process of going from measurements of the differential cross-sections to nucleon form factors is nontrivial and involves modeling [1,31,43]. As already stated, we have two reasons to analyze the experimental data: to compare them against the lattice data over the range 0 < Q 2 0.8 GeV 2 , and to test the efficacy of the dipole and z-expansion fit ansätze.…”
Section: Dependence On Lattice Scale Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The so-called proton radius puzzle appears to be resolved. The puzzle emerged in 2010 when a muonic hydrogen measurement of the n = 2 Lamb shift [1] found that the very accurately measured proton charge radius R E = 0.8409(4) fm (or using a more conservative, model-independent analysis R E = 0.8413 (15) fm) disagreed with previous measurements of regular atomic hydrogen intervals [2], quoted in 2014 as R E = 0.8751(61) fm, as well as the state-of-the-art Mainz e − p scattering experiment (MAMI) [3,4] with a result of which links atomic units to SI [7,12], and settling on it and on the proton charge radius opens the possibility for further tests of quantum electrodynamics in atomic hydrogen. In its most recent update CODATA has adopted the small (muonic) radius value of 0.8414 (19) fm [13].…”
Section: Introductionmentioning
confidence: 99%
“…The issues of fitting and extrapolation of the form-factor data have lately been under intense discussion, see, e.g., Refs. [14,[25][26][27]. Similar extrapolation problems should exist in the extractions based on lattice QCD, since the lowest momentum-transfer therein is severely limited by the finite volume.…”
Section: Introductionmentioning
confidence: 99%